ANALISIS KINERJA KEUANGAN PEMERINTAH DAERAH KOTA SURAKARTA TAHUN 2017-2019 - Vitalis Ari Widiyaningsih; Margaretha Prihatiningsih (Media Akuntansi, 2021)
This study aims to determine the Financial Performance of Surakarta City's Regional Revenue for the 2017-2019 period and find out the Financial Performance of Surakarta City's Regional Expenditure for the 2017-2019 period. This research is a quantitative descriptive study, namely research that seeks to describe the current problem solving using numbers, starting from data collection, interpretation of the data and the appearance of the results. Data collection techniques used in this study using documentation techniques. The data used is secondary data in the form of the Surakarta City Regional Budget Realization Report for 2017-2019. The expected results of this study indicate that the Financial Performance of Surakarta City's Regional Revenue is generally said to be good. Revenue performance is good as seen from the Regional Income Variance, Regional Income Growth, Regional Income Financial Ratios seen from the Degree of Decentralization, Regional Financial Dependence Ratio, Effectiveness and Efficiency Ratio of Regional Taxes, and the Degree of BUMD Contribution. In general, the performance of the Surakarta Regency Government's Regional Expenditure Financial Performance can be said to be good. Expenditure performance is good as seen from the Regional Expenditure Variance, Regional Expenditure Growth, and Shopping Harmony.